2015
DOI: 10.1590/0102-311x00029215
|View full text |Cite
|
Sign up to set email alerts
|

As interações entre os atores no retorno ao trabalho após afastamento por transtorno mental: uma metaetnografia

Abstract: Resumo Transtornos mentais repercutem no mundo do trabalho. Estudos sobre interações entre os atores envolvidos no retorno ao trabalho são raros. A metaetnografia presta-se a sintetizar estudos qualitativos através da interpretação e comparação contínua dos conceitos presentes nos artigos. Este estudo propõe uma metaetnografia sobre as interações entre os atores sociais envolvidos no processo de retorno ao trabalho após afastamento por transtornos mentais. Visa: (1) explorar as interações entre os atores socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
20

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 31 publications
(100 reference statements)
0
8
0
20
Order By: Relevance
“…Com isso, ao pautar sua atuação a partir do direito à saúde e à vida, a terapia ocupacional tem sido desafiada a inovar, transformar e produzir novas formas de ação junto às populações vulnerabilizadas pela deficiência e pelo estigma 17 . Nesta direção, os programas de reabilitação articulados a partir da superação da lógica individualista têm sido recomendados 18 .…”
Section: Resultsunclassified
“…Com isso, ao pautar sua atuação a partir do direito à saúde e à vida, a terapia ocupacional tem sido desafiada a inovar, transformar e produzir novas formas de ação junto às populações vulnerabilizadas pela deficiência e pelo estigma 17 . Nesta direção, os programas de reabilitação articulados a partir da superação da lógica individualista têm sido recomendados 18 .…”
Section: Resultsunclassified
“…The concepts extracted from the articles revealed that in a society in which differences are viewed as "flaws" or "handicaps", the sense of parenthood is permeated by the demand to produce and develop healthy, cooperative, and efficient individuals. According to prevailing capitalist logic, a body that fails to produce profit is considered invalid 26 . Fathering or mothering a child with disability thus becomes a dehumanizing experience, to the extent that it strips these men and women of the condition of equality with others, marking them as inferior 27 .…”
Section: Disability and Ideal Parenthoodmentioning
confidence: 99%
“…There was a low number of researches that looked at mental illnesses and disorders 37,[39][40][41] , despite its expressive prevalence, reaching between 20% and 56% of the Brazilian adult population, mainly women and workers 78 . The impact on the quality of life of these people and the repercussions they have on the world of work put mental disorders as a serious public health problem 79,80 .…”
Section: Chart 3 Characterization Of the Profile Of Physical Diseasementioning
confidence: 99%